Comparison of carbon isotope ratio measurement of the vanillin methoxy group by gc-irms and 13c-qnmr - Greule, Markus; Le, Phuong Mai; Meija, Juris; Mester, Zoltán; Keppler, Frank (Journal of the American Society for Mass Spectrometry, 2024)
Site-specific carbon isotope ratio measurements by quantitative 13C NMR (13C-qNMR), Orbitrap-MS, and GC-IRMS offer a new dimension to conventional bulk carbon isotope ratio measurements used in food provenance, forensics, and a number of other applications. While the site-specific measurements of carbon isotope ratios in vanillin by 13C-qNMR or Orbitrap-MS are powerful new tools in food analysis, there are a limited number of studies regarding the validity of these measurement results. Here we present carbon site-specific measurements of vanillin by GC-IRMS and 13C-qNMR for methoxy carbon. Carbon isotope delta (δ13C) values obtained by these different measurement approaches demonstrate remarkable agreement; in five vanillin samples whose bulk δ13C values ranged from −31‰ to −26‰, their δ13C values of the methoxy carbon ranged from −62.4‰ to −30.6‰, yet the difference between the results of the two analytical approaches was within ±0.6‰. While the GC-IRMS approach afforded up to 9-fold lower uncertainties and required 100-fold less sample compared to the 13C-qNMR, the 13C-qNMR is able to assign δ13C values to all carbon atoms in the molecule, not just the cleavable methoxy group.
Im Titel ist 13 hochgestellt
Published online 28 November 2023, published in issue 3 January 2024
Gesehen am 14.03.2024